Competencies and Experiences Needed by Entry Level International Agricultural Development Practitioners - Nathan W Conner; Grady Roberts; Amy Harder (Journal of International Agricultural and Extension Education, 2013)
The use of competencies within extension can be an effective way of training and developing extension practitioners (Stone, 1997). In preparation for careers in tomorrow’s agricultural sector, the National Research Council (2009) recognized the need to expose college students to international perspectives. The purpose of this study was to determine the competencies and experiences that entry level agricultural development practitioners need in order to successfully work in an international setting. A modified Delphi method was used to achieve this purpose. A panel of experts in international agricultural development from non–government organizations, government organizations, and academic institutions were selected through snowball sampling (Goodman, 1961). The panelists agreed on 26 competencies and 7 experiences that entry level agricultural development practitioners working internationally should have before entering the profession. The results of this study should be used when planning, designing, and implementing agricultural extension education programs at the university level.
Keywords: Competencies; International Agricultural Development; Modified Delphi Method; Extension Education